Estimating the stopping power distribution during proton therapy: A proof of concept - Ferrero, Veronica; Werner, Julius; Cerello, Piergiorgio; Fiorina, Elisa; Vignati, Anna; Pennazio, Francesco; Rafecas, Magdalena (Frontiers in Physics, 2022)
Objective. We introduce a new treatment verification technique to estimate the primary particle's stopping power from prompt gamma timing measurements in proton therapy. Approach. The starting point is the Spatio-temporal Emission Recostruction technique, which provides the time-depth distribution of the emitted prompt photons with a multiple Prompt-Gamma Timing detector setup based on Lanthanum Bromide crystals. A dedicated formalism based on an analytical approximation of the stopping power is developed to obtain the desired information. Its performance is evaluated in a proof of concept configuration via Monte Carlo simulations of monochromatic proton beams impinging on a homogeneous PMMA phantom. Main Results. Results indicate stopping power estimations as good as 3.8% with respect to NIST values, and range estimations within 0.3 cm (standard deviation), when considering 250 ps FWHM timing resolution. Significance. The current study shows, for the first time, the feasibility of evaluating the stopping power of primary beams with a technique that can be performed in-vivo, opening up new possibilities in the field of treatment verification and therapy optimization.